METTL3, an Independent Adverse Prognostic Factor for AML, Promotes the Development of AML by Modulating the PGC‐1α–MAPK Pathway and PGC‐1α–Antioxidant System Axis - Yuqian Tang; Xiaoyan Liu; Wu Ye; Xiaojia Wang; Xiaoyu Wei; Yiwen Du; Ying Zhang; Yuping Gong (Cancer Medicine)
ABSTRACT Background m6A represents a prevalent epigenetic modification of mammalian mRNAs. Studies have demonstrated that m6A RNA methylation‐modifying enzymes play crucial roles in the onset and progression of AML. However, their clinical relevance remains undefined, and the mechanisms underlying their modulation of AML have yet to be elucidated. Results The expression levels of the m6A RNA‐modifying enzymes METTL3, METTL14, WTAP, FTO and ALKBH5 were elevated in AML patients. METTL3‐positive AML is often accompanied by DNMT3A mutations and is also an independent poor prognostic factor for AML patients. Following METTL3 knockdown, we observed a decrease in the m6A level of the mitochondrial oxidative stress gene PGC‐1α in K562 and MV4‐11 cells. We analyzed the expression levels of PGC‐1α and METTL3 mRNA in 105 patients with primary AML. The expression levels of PGC‐1α and METTL3 mRNA were positively correlated. Similar to METTL3 knockdown, PGC‐1α gene knockdown resulted in increased phosphorylation of the key signaling molecules P38, c‐Jun and ERK1/2 in the MAPK signaling pathway, and decreased mRNA levels of SOD1, GPX1, catalase and UCP2 in the antioxidant system of K562 cells. Analysis of the TCGA and GSE13159 datasets, along with samples from West China Hospital, revealed that patients exhibiting high PGC‐1α expression had a poor prognosis. Conclusion The m6A methylation‐modifying enzyme METTL3 is an independent prognostic factor for poor prognosis in AML patients. PGC‐1α is a downstream signaling molecule of METTL3, and METTL3 affects its expression by regulating the m6A level of PGC‐1α. PGC‐1α acts as an oncogene in AML by affecting the MAPK pathway and antioxidant system.